PAPAN PARTIKEL DARI SERBUK KAYU DAN LIMBAH PENYULINGAN KULIT KAYU GEMOR (Alseodaphne spp.) - Budi Tri Cahyana (Kementerian Perindustrian, 2013)
Utilization of gemor bark (Alseodaphne spp) distillation waste for particle board had been carried out. The aim of this research was physical mechanical from wood sawdust waste mixed with gemor bark distillation waste which properties physically and mechanically meet quality requirements. The raw materials used were sawdust mixed with gemor bark distillation waste which mashed16 mesh and the adhesive used were starch and PVAC. Composition variety of the mixture of wood sawdust waste particles and gemor bark distillation waste particle 50%: 50%, 60%: 40%., 70%: 30% with 5% adhesive. The results showed that highest average of modulus of rupture (27,55 kg/cm2) was obtained in 70% : 30% comparison of sawdust and gemor bark distillation waste with starch adhesive (a3b1) and the density average was 0.75 gr/cm3. The highest average of modulus of elasticity (351,50 kg/cm2) was in composition of 60%: 40% with starch adhesive (a2b1) and the density average was 0.69 gr/cm3. The highest average of tensile strength (4,11 kg/cm2) was obtained in composition of 50%: 50% with starch adhesive and the density average was 0.79 gr/cm3.Keywords: sawdust wood, distillation waste, gemor bark, particle board